Winter cold-tolerance thresholds in field-grown Miscanthus hybrid rhizomes - Peixoto, Murilo de Melo (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.